Prospecting for science in the former Soviet Union - Rhea, John
The stampede is on to acquire the scientific talent being stranded by the disintegration of the Soviet Union. Russian scientists (and those from other former republics as well as other Eastern European nations) offer unique talents nurtured during their semi-isolation from the West. Led by the United States, Japan, Germany, and the other industrialized nations, this talent search seeks to acquire valuable basic research that can be turned into marketable products. But those who have already entered the fray sound a note of caution : Don't be misled by what look like bargain basement wage rates. Establish mutually beneficial relationships, take plenty of time to do it right and, most of all, be patient. You're dealing with an entirely different culture, they warn, but the ultimate payoff should offset the initial logistics problems.
John Rhea reports on how Western companies can take advantage of the opportunities that await them.
The collapse of the Soviet Union offers immense opportunities to industry, but Western companies must stick to proven business methods.